Factores Que Afectan Al Cultivo De CaÃ±a De AzÃºcar Para ProducciÃ³n De Bioetanol En Ecuador - Castro-Armijos, Cristhian Jover; Prado-Carpio, Eveligh; Paladines-Romero, JosÃ© Roberto; Cervantes-Ãlava, Abrahan (European Scientific Journal, ESJ, 2017)
The purpose of this article is to predict the impact of variables planted area, rainfall and temperature on production. The research is focused on the analysis of agricultural statistical information from Ecuador, which was compiled from institutions such as the Surface Survey and Continuing Agricultural Production (ESPAC) and the Agricultural Information System (SINAGAP). For the statistical analysis of the information the multiple linear regression method was used using the software SPSS 21. The results obtained show that 51.86% of the variability is predicted by the variable planted area. It is important to continue producing gasoline blends with ethanol from sugarcane and diesel with biodiesel, focusing this on the production transformation framed in the National Plan for Good Living 2013-2017, thus promoting energy security, reducing emissions of Longterm greenhouse effect. The results presented predict the variables that most influence the agricultural production of sugar cane.